(untitled) (Construction Economics and Building, 2025)
Social sustainability has been acknowledged as an essential component for delivering sustainable development objectives. While the importance of social sustainability has been well recognised by many construction industry practitioners, its core requirements have remained undefined. Many of such social sustainability concepts have remained implicit and undefined. In some case, they have been ‘concealed behind a seemingly random choice of common socio-political indicators hence making social sustainability requirements very difficult for practitioners to clearly specify and prioritise in an explicit manner and deliver it in practical terms. This study investigates the degree of consideration given to the promotion of social sustainability factors by practitioners engaged in the delivery of sustainable regeneration projects in the UK. It draws data from 15 and 122 practitioners through semi-structured interviews and questionnaire survey respectively, from practitioners who participated in the study. The results reveal that, health and safety issues were the most promoted among the other six key social sustainability issues considered by majority of practitioners. The findings indicate that various efforts and legislations initiated by the UK government to improve health and safety practices within the construction industry had played a key role on practitioners’ attitude towards the promotion of health and safety issues in their practices.